A comparative Study of Some Physical Fitness Component’s’ Test Results for Players Applying to The National Center for Gifted In Taekwondo, Wrestling and Boxing Aged 10 – 15 Years Old - Mohammed, Amwaj (Journal of Physical Education, 2021)
The research aimed at comparing some physical fitness components (stamina, explosive strength, transitional speed, agility, etc) in players applying for the national center of gifted in taekwondo, wrestling, and boxing aged (10 – 15) years old. The researcher used the descriptive method on (107) divided (26) for taekwondo, (43) for wrestling, (34) for boxing. The data was collected and treated using proper statistical operations to conclude that players applying for taekwondo, wrestling and judo had no significant differences. On the other hand, there are significant differences in stamina, transitional speed, and explosive strength. In general, athletes applying for boxing surpassed other athletes in all physical abilities.